CRISPR Gene Drive Efficiency and Resistance Rate Is Highly Heritable with No Common Genetic Loci of Large Effect - Champer, Jackson (Genetics, 2019)
Gene drives could allow for control of vector-borne diseases by directly suppressing vector populations or spreading genetic payloads designed to reduce pathogen transmission. Clustered regularly interspaced short palindromic repeat (CRISPR) homing gene drives work by cleaving wild-type alleles, which are then converted to drive alleles by homology-directed repair, increasing the frequency of the drive in a population over time. However, resistance alleles can form when end-joining repair takes place in lieu of homology-directed repair. Such alleles cannot be converted to drive alleles, which would eventually halt the spread of a drive through a population. To investigate the effects of natural genetic variation on resistance formation, we developed a CRISPR homing gene drive in Drosophila melanogaster and crossed it into the genetically diverse Drosophila Genetic Reference Panel (DGRP) lines, measuring several performance parameters. Most strikingly, resistance allele formation postfertilization in the early embryo ranged from 7 to 79% among lines and averaged 42 ± 18%. We performed a genome-wide association study using our results in the DGRP lines, and found that the resistance and conversion rates were not explained by common alleles of large effect, but instead there were several genetic polymorphisms showing weak association. RNA interference knockdown of several genes containing these polymorphisms confirmed their effect, but the small effect sizes imply that their manipulation would likely yield only modest improvements to the efficacy of gene drives.